(untitled) (Research, Society and Development, 2022)
Pregnancy and puerperium are a phase of a woman’s life marked by a series of physiological, social, family and psychological changes that trigger manifestations of ambiguous feelings that can cause psychological imbalance in women and, consequently, in their interaction with the baby. During this period, women are more susceptible to the onset of mental problems when compared to other stages of life, as their physical and psychosocial defenses are directed towards the protection and vulnerability of the baby. In this sense, this study seeks to characterize the prevalence and factors associated with postpartum feelings in postpartum women. Therefore, this research is an integrative literature review, using articles, books, manuals, monographs, dissertations and theses. The study made it possible to verify that women experience a series of changes in the postpartum period, from the considerable reduction in sleep hours to the loss of their autonomy, since their entire routine is controlled according to the baby’s schedule. This period brings a series of new feelings, which start to participate in their decision-making, from that moment onwards. It is concluded that this study presented as relevance the knowledge about the experience of contemporary women in face of motherhood and how she begins to define its representation, as it was found that despite so many important roles in society, in addition to being a mother, Motherhood continues to be a major event for women, if not the most important in their lives.